LANGUAGE SCHOOLS AND FOREIGN LANGUAGE STUDYING PROGRAMS IN PORTUGAL - Iryna Hritchenko (Pavlo Tychyna Uman State Pedagogical University, 2017)
The article is devoted to the description and characterizing of language schools and foreign language studying programs in Portugal. The relevance of language learning for professional, mobility, self-developing means is shown. The main courses and programs are observed and the advantages and disadvantages of each of them are given. It is stated that Portuguese courses mostly follow the Common European Framework of Reference for Languages. A small synopsis of the abilities for each level is presented. Numerous language schools for foreigners to learn Portuguese (Iberlínguas, Languages Abroad, Amerispan, Nikitas Language Abroad School, Portuguese Connection Language School, Eurolingua Institute, CIAL Centro de Linguas, Apple Languages, Escola Europeia de Línguas (EEL), Fast Forward Language Institute, International House Portugal, Margarida's School, Mundilingua) are described. It is pointed out that along with language courses Portugal also offers different language programs for people of all ages with various communicative needs. The description of budget, adventure, family and medical programs is given. The additional opportunities for foreigners learning Portuguese (surf classes, guided excursions and sightseeing, international parties, Fado nights, tile painting workshops, cooking classes) are shown. The private tuition advantages are presented. The free language studying with teachers' volunteers is shown. The main advantages and disadvantages of this method of learning are emphasized. It is pointed out that the choice of any course and program should be made considering the following characteristics: place, intensity of the course, language level, purpose of studying and cost. The further investigation which can include the analysis of language courses and programs for Portuguese people, their pros and cons, main purposes of teaching foreign languages is mentioned.